Are Financial Market Anomalies Real? Evidence from Stock Markets in Five Countries - Ficik, Jozef; Musílek, Petr, 1965-; Derner, Tomáš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
The financial market anomaly can be characterized as the event when observed stock returns differentiate from those expected by concrete pricing model. Many anomalies have been detected so far, and some of them vanished, while other persisted, after they had been published by academics and researchers. The aim of this thesis is to investigate the potential presence of selected types of anomalies in the financial markets and to provide relevant empirical evidence. The theoretical section will supply the reader with the descriptions of several types of financial market anomalies and the results of past studies documenting the existence of these anomalies, with possible reasons justifying the presence of this phenomenon. The analytical section will focus on the few selected anomalies and test whether they are still present in the selected financial markets.
Vedoucí práce: Petr Musílek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses